2009
DOI: 10.1002/jcb.22061
|View full text |Cite
|
Sign up to set email alerts
|

Isoform‐specific cleavage of 14‐3‐3 proteins in apoptotic JURL‐MK1 cells

Abstract: The proteins of 14-3-3 family are substantially involved in the regulation of many biological processes including the apoptosis. We studied the changes in the expression of five 14-3-3 isoforms (beta, gamma, epsilon, tau, and zeta) during the apoptosis of JURL-MK1 and K562 cells. The expression level of all these proteins markedly decreased in relation with the apoptosis progression and all isoforms underwent truncation, which probably corresponds to the removal of several C-terminal amino acids. The observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(46 reference statements)
6
11
0
Order By: Relevance
“…Z-DEVD-fmk at 20 µM prevented 14-3-3β but not 14-3-3θ depression by H 2 O 2 (Figure 2B). The result is consistent with a previous report that caspase 3 degrades 14-3-3β but not θ [19]. H 2 O 2 -induced 14-3-3β and θ reduction was reversed by pretreatment with Wy14,643 (Figure 2A).…”
Section: Resultssupporting
confidence: 93%
“…Z-DEVD-fmk at 20 µM prevented 14-3-3β but not 14-3-3θ depression by H 2 O 2 (Figure 2B). The result is consistent with a previous report that caspase 3 degrades 14-3-3β but not θ [19]. H 2 O 2 -induced 14-3-3β and θ reduction was reversed by pretreatment with Wy14,643 (Figure 2A).…”
Section: Resultssupporting
confidence: 93%
“…Western blotting conducted on apoptotic cell lysates detected a proteolytic fragment of ∼37 kD for Hsp90 alpha (N-terminus) and of ∼50 kD (C-terminus) for Hsp90 beta (Figure 4) consistent with the sizes predicted for caspase cleavage. For 14-3-3 beta, gamma and epsilon, the molecular weight of the cleaved form was only marginally smaller than that of the full length proteins, mirroring what has already been described for caspase-mediated cleavage of 14-3-3 proteins [35].…”
Section: Discussionsupporting
confidence: 79%
“…This protein is downregulated during apoptosis of JURL-MK1 and K562 cells. 26 We also observed increased expression of cytokeratin 18 (a marker of cell death) and cytokeratin 19, and decreased expression of cytokeratin 8 after DAMTC treatment. Cytokeratins are important constituent of intermediate filaments and several investigators have shown an important role of these cytokeratins in signal transduction and apoptosis pathways.…”
Section: Discussionsupporting
confidence: 50%